Subdiffusion of nonlinear waves in two-dimensional disordered lattices - Laptyeva TV; Bodyfelt JD; Flach S (EPL ASSOCIATION, EUROPEAN PHYSICAL SOCIETY)
We perform high-precision computational experiments on nonlinear waves in two-dimensional disordered lattices with tunable nonlinearity. While linear wave packets are trapped due to Anderson localization, nonlinear wave packets spread subdiffusively. Various speculations on the growth of the second moment as t α are tested. Using fine statistical averaging we find agreement with predictions from Flach S., Chem. Phys., 375 (2010) 548, which supports the concepts of strong and weak chaos for nonlinear wave propagation in disordered media. We extend our approach and find potentially long-lasting intermediate deviations due to a growing number of surface resonances of the wave packet. © 2012 EPLA.
Keywords: Science & Technology; Physical Sciences; Physics, Multidisciplinary; Physics; PHYSICS, MULTIDISCIPLINARY; ANDERSON LOCALIZATION; GASES; TRANSPORT; CROSSOVER; SYSTEMS; CHAOS; 01 Mathematical Sciences; 02 Physical Sciences